2013
DOI: 10.1242/jcs.1125880
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β signals through tau to drive ectopic neuronal cell cycle re-entry in Alzheimer's disease

Abstract: SummaryNormally post-mitotic neurons that aberrantly re-enter the cell cycle without dividing account for a substantial fraction of the neurons that die in Alzheimer's disease (AD). We now report that this ectopic cell cycle re-entry (CCR) requires soluble amyloid-b (Ab) and tau, the respective building blocks of the insoluble plaques and tangles that accumulate in AD brain. Exposure of cultured wild type (WT) neurons to Ab oligomers caused CCR and activation of the non-receptor tyrosine kinase, fyn, the cAMP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
149
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 155 publications
(160 citation statements)
references
References 53 publications
6
149
4
1
Order By: Relevance
“…The upstream mediators driving tau‐associated cellular senescence in AD and PSP also remain unknown; however, it is tempting to speculate that tau‐induced cell cycle re‐entry may be involved (Arendt, 2012). Aberrant cell cycle re‐entry causes neuronal apoptosis and AD‐associated pathology (Park, Hallows, Chakrabarty, Davies, & Vincent, 2007) and requires soluble tau (Seward et al, 2013). The observed increase in NFT‐associated Cdkn1a and Cdkn2a gene expression may allow stressed neurons to abort cell cycle re‐entry and enter a cellular state similar to cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…The upstream mediators driving tau‐associated cellular senescence in AD and PSP also remain unknown; however, it is tempting to speculate that tau‐induced cell cycle re‐entry may be involved (Arendt, 2012). Aberrant cell cycle re‐entry causes neuronal apoptosis and AD‐associated pathology (Park, Hallows, Chakrabarty, Davies, & Vincent, 2007) and requires soluble tau (Seward et al, 2013). The observed increase in NFT‐associated Cdkn1a and Cdkn2a gene expression may allow stressed neurons to abort cell cycle re‐entry and enter a cellular state similar to cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, putative dimers and trimers containing both conventional and pE-modified Aβ species were detected more commonly in brain cytosol collected post-mortem from AD patients than from normal age-matched controls, and transgenic mice that produced Aβ3(pE)-x experienced massive gliosis and neuron death in the hippocampus by disease. 5,9,11,46,[48][49][50]79,80 At least some of these Aβ-tau connections are indirect, such as Aβ induced activation of protein kinases, which then catalyze abnormal tau phosphorylation. 11,45,47,51,52 There is also evidence, though, for a direct pathogenic connection between Aβ and tau.…”
Section: Are Tau Prions Seeded By Aβ Prions?mentioning
confidence: 99%
“…5,9,11,46,[48][49][50]79,80 At least some of these Aβ-tau connections are indirect, such as Aβ induced activation of protein kinases, which then catalyze abnormal tau phosphorylation. 11,45,47,51,52 There is also evidence, though, for a direct pathogenic connection between Aβ and tau. In the absence of any other proteins or peptides, Aβ can bind to tau 43 and tau monomers can be induced to oligomerize in vitro after exposure to low substoichiometric levels of Aβ oligomers.…”
Section: Are Tau Prions Seeded By Aβ Prions?mentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon was expounded upon by Roberson and colleagues, who showed that learning and memory deficits present in a mouse line overexpressing mutant human APP were mitigated by crossing the animals to a tau null background [127]. Further studies have shown that a variety of toxic effects and cellular phenotypes due to Aβ, such as NMDA receptor related excitotoxicity [122], Aβ-induced microtubule loss [136], inhibition of mitochondrial transport [137], impairment of LTP [138], synaptic damage [139], aberrant cell-cycle re-entry [140] and overall cell toxicity [141] could be ameliorated through loss of tau expression. This wealth of data identifying tau-dependent phenotypes has led many to propose tau depletion as a possible therapy in tau-related disorders [142].…”
Section: Tau Knockout Micementioning
confidence: 99%